Borle's triangle: A reliable anatomical landmark for ease of identification of facial nerve trunk during parotidectomy - Rajiv M. Borle; Anendd Jadhav; Nitin Bhola; Pawan Hingnikar; Prafulla Gaikwad (Elsevier, 2019)
Purpose: An accurate understanding of the anatomy, identification and preservation of facial nerve is critical in performing successful functional parotidectomies. The current literature is replete with inconsistencies of various landmarks when used alone for identification of facial nerve trunk (FNT). The purpose of the paper is to introduce a new anatomical triangle, Borle's triangle (BT) for safer and reliable operative identification of FNT during parotodectomies. Patients and methods: Between Aug 2014 and Dec 2017, twelve patients who reported with unilateral disease of the parotid gland with intact facial nerve function who underwent superficial or complete parotidecomies were included in the study. BT was conceptualized by intersection of three imaginary lines drawn along anatomical structures and forming a triangle comprising of angles a, b and c. Results: Introperatively, BT helped reliably identify the FNT and its branches successfully in all the cases. The mean distance of FNT from angle b was found to be 12.18 ± 1.7 mm. Transient neurological deficits with one or more branches were seen in four cases whilst, one case had transient deficit with all the five peripheral branches. All of them spontaneously resolved completely by the end of three months post operatively. Conclusions: When used in isolation, substantial variations exist in distances measured from anatomic landmarks to the main FNT in the literature. The BT utilizes three commonly used anatomical landmarks. It predictably helps in proper anatomic orientation, identification and preservation of FNT and branches with ease in parotidectomies.